Adiponectin/AdiopR1 signaling prevents mitochondrial dysfunction and oxidative injury after traumatic brain injury in a SIRT3 dependent manner - Shenghao Zhang; Xun Wu; Jin Wang; Yingwu Shi; Qing Hu; Wenxing Cui; Hao Bai; Jinpeng Zhou; Yong Du; Liying Han; Leiyang Li; Dayun Feng; et al. (Redox Biology, 2022)
Mitochondrial dysfunction and oxidative injury, which contribute to worsening of neurological deficits and poor clinical outcomes, are hallmarks of secondary brain injury after TBI. Adiponectin (APN), beyond its well-established regulatory effects on metabolism, is also essential for maintaining normal brain functions by binding APN receptors that are ubiquitously expressed in the brain. Currently, the significance of the APN/APN receptor (AdipoR) signaling pathway in secondary injury after TBI and the specific mechanisms have not been conclusively determined. In this study, we found that APN knockout aggravated brain functional deficits, increased brain edema and lesion volume, and exacerbated oxidative stress as well as apoptosis after TBI. These effects were significantly alleviated after APN receptor agonist (AdipoRon) treatment. Moreover, we found that AdipoR1, rather than AdipoR2, mediated the protective effects of APN/AdipoR signaling against oxidative stress and brain injury after TBI. In neuron-specific AdipoR1 knockout mice, mitochondrial damage was more severe after TBI, indicating a potential association between APN/AdipoR1 signaling inactivation and mitochondrial damage. Mechanistically, neuron-specific knockout of SIRT3, the most important deacetylase in the mitochondria, reversed the neuroprotective effects of AdipoRon after TBI. Then, PRDX3, a critical antioxidant enzyme in the mitochondria, was identified as a vital downstream target of the APN/SIRT3 axis to alleviate oxidative injury after TBI. Finally, we revealed that APN/AdipoR1 signaling promotes SIRT3 transcription by activating the AMPK-PGC pathway. In conclusion, APN/AdipoR1 signaling plays a protective role in post-TBI oxidative damage by restoring the SIRT3-mediated mitochondrial homeostasis and antioxidant system.